Deoxyguanosine-resistant Leukemia L1210 Cells: Loss of Specific Deoxyribonecleoside Kinase Activity - Cory, Ann H.; Shibley, Ivan A.; Chalovich, Joseph; Cory, Joseph G. (East Carolina University, 1993)
A mouse leukemia L1210 cell line was selected for resistance to deoxyguanosine. The deoxyguanosine-resistant cells (dGuo-R) were 126-fold less sensitive to deoxyguanosine than the wild-type cells. The IC50 values for araC and araG were increased, but only 10-12-fold in the dGuo- R cells when compared with the wild-type cells. The dGuo-R cell line showed an increased level of resistance to 2-fluoro-2'-deoxyadenosine and 2-fluoroadenine arabinoside (11-14-fold), but essentially no increase in resistance to deoxyadenosine or adenine arabinoside. Deoxyribonucleoside kinase activity was decreased only slightly (19%) when deoxycytidine was utilized as substrate; when cytosine arabinoside or deoxyguanosine was used as the substrate, the kinase activity in the extracts from the dGuo-R cells was only 10% of the enzyme activity in the extracts from the wild-type cells. The determination of the kinetic parameters, Km and Vmax, indicated that there were marked decreases in the Vmax values for deoxyguanosine and cytosine arabinoside as substrates, but not for deoxycytidine as substrate; the Km values for deoxycytidine and cytosine arabinoside were increased in the extracts from the dGuo-R cells. By use of high-performance liquid chromatography, the kinase activities in the extracts from the wild-type and resistant cells could be resolved. There was the specific loss of kinase activity toward cytosine arabinoside and deoxyguanosine as substrates. These data indicate that the dGuo-R cells have decreased levels of a specific deoxyribonucleoside kinase activity. Originally published Journal of Biological Chemistry, Vol. 268, No. 1, Jan 1993
Keywords: Deoxyguanosine resistance; Leukemia cells; Deoxyribonucleoside kinase activity